Interpersonal values related to the adjustment of maguindanaon college student - Carim, Paz Ocho
The objective of the study is to examine the interpersonal values of the Maguindanaon Muslim college students and how these values relate to their adjustment. Eight value dimensions studied are the following: support, conformity, recognition, independence, benevolence, leadership, family solidarity, and social acceptance. The researcher looked into the differences in these interpersonal values considering the personal variables of sex, age, civil status, and curriculum year levels of the respondents. The study likewise attempts to identify some values that can be used as predictors of home, school, social and emotional adjustments.